Pengaruh Syariah Marketing, Kualitas Pelayanan, Citra Merek terhadap Kepuasan Konsumen pada Asuransi Jiwa Syariah Bumiputera Cabang Bandar Lampung - Sari, Nuri Anjar; Indriyani, Susi (Jurnal Enterpreneur dan Bisnis (JEBI), 2022)
The purpose of this research is to know how the influence of sharia marketing, service quality, brand image on customer satisfaction in sharia insurance companies. The sampling technique used in the research based on the Krejcie table with error levels 10%. The analysis tool used in this research is multiple linear regression. To get  test results in this research, it should be Validity test, Reliability, Classical Assumption Test, and Hypothesis Test. In this research at simultaneous result (Test F) showed influence of sharia marketing, service quality, brand image are simultaneously influence of customer statisfaction and partial test sharia marketing has a significant influence on the customer statisfaction, service quality has a significant influence of the customer statisfaction, brand image has a significant influence on the customer statisfaction. The advice that can be proposed in this research is should the company improve sharia marketing for the proses of maintaining customers by building long-term relationship with existing customer can be achieved and can increase profits for the company.